Understanding the purposes for keeping cattle and their perceived traits by farmers in Oromiya Regional State, Ethiopia - Dorland, H.A. van; Ayalew, W.; Tolessa, A.; Rowlands, G.J.; Rege, J.E.O. (Ethiopian Society of Animal Production, 2004)
The genetic diversity within indigenous livestock breeds of countries like Ethiopia results from the diverse ways in which these resources have been used to support human livelihoods and their ability to cop with the specific environments in which they have been kept. The genes and gene combinations that indigenous breeds carry may be useful in future. However, little documented empirical evidence is available in Ethiopia on the comparative merits of different indigenous genetic resources, information that is needed to rationalise the best ways to sustain their utilisation. Data have been collected in a livestock breed characterisation survey carried out in Oromiya Regional State from July to December 2001 (sample size of 5,587 households). Analysis of data collected on cattle are Reported on the reasons given by- farmers for keeping cattle, by agro-ecological zone and production system, and on their perceived assessments of the different attributes possessed by their cattle in terms of productivity and adaptability to the environment. The results showed that cattle are kept for multiple purposes, both across agro-ecological zones and production systems. However, purposes vary with production system. Traction (males) ranked highest, followed by milk (females) and reproduction/breeding (males and females) in both crop-livestock and agro-pastoral systems. Manure production was also considered important by most crop/livestock and agro-pastoralist farmers, but as a secondary rather than a primary purpose. In contrast, reproduction/breeding requirements received higher ranks in pastoralist systems and, for female, requirements for breeding outranked the importance of milk production. On average a fifth of farmers listed traction among the uses for female cattle. Farmers' perceptions of the quality of their cattle in terms of adaptation and productivity also varied across production systems. Productivity traits were generally rated higher than adaptability traits, especially by agro-pastoralists and pastoralists. Approximately three quarters of farmers across all production systems and agro-ecological zones rated the work output of their cattle to be 'good'. In contrast, less than half of the farmers, in particular those managing crop/livestock systems, rated adaptability traits as `good', with the proportion of farmers rating disease and drought tolerance to be `good' being particularly low. Pastoralists showed the highest satisfaction levels in terms of cattle productivity but were less satisfied than agropastoralists in terms of adaptability of their cattle to the environment.